2002
DOI: 10.1034/j.1600-6143.2002.20406.x
|View full text |Cite
|
Sign up to set email alerts
|

The Immunobiology of Inductive Anti-CD40L Therapy in Transplantation: Allograft Acceptance is Not Dependent Upon the Deletion of Graft-Reactive T Cells

Abstract: CD40-CD40L costimulatory interactions are crucial for allograft rejection, in that treatment with anti-CD40L mAb markedly prolongs allograft survival in several systems. Recent reports indicate that costimulatory blockade results in deletion of graft-reactive cells, which leads to allograft tolerance. To assess immunologic parameters that were influenced by inductive CD40-CD40L blockade, cardiac allograft recipients were treated with multiple doses of the anti-CD40L mAb MR1, which was remarkably effective at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 52 publications
5
40
0
Order By: Relevance
“…In fact, this has been the major controversial issue in the mechanism of CD154 blockade in promoting allograft survival (14,15,17). The results of our experiments in in vivo setting of primary tolerant recipients have confirmed several previous findings primarily from adoptive transfer cell systems, that CD4…”
Section: Cd8supporting
confidence: 80%
See 1 more Smart Citation
“…In fact, this has been the major controversial issue in the mechanism of CD154 blockade in promoting allograft survival (14,15,17). The results of our experiments in in vivo setting of primary tolerant recipients have confirmed several previous findings primarily from adoptive transfer cell systems, that CD4…”
Section: Cd8supporting
confidence: 80%
“…To identify the type of CD4 ϩ Treg that controls alloreactive CD8 ϩ T cells and maintains graft survival in our model, we used anti-CD25 mAb treatment, which has been shown to efficiently deplete CD4 ϩ CD25 ϩ T cells in both autoimmune disease and tumor models (14,15). Depletion of CD4 ϩ CD25 ϩ cells resulted in the rejection of donor-type skin grafts in ϳ70% of long-term hosts, albeit with somewhat delayed kinetics (MST Ϯ SD ϭ 14 Ϯ 2 days; n ϭ 4, Fig.…”
Section: Induction and Function Of Cd4mentioning
confidence: 99%
“…This was consistent with previous studies showing that blocking the CD27/70 pathway effectively inhibited the function and generation of memory T cells [28,29]. Furthermore, we found that this treatment regimen abrogated the production of IgG1/IgG2a alloantibodies in recipient mice, were consistent with a prior study by Nathan et al demonstrating that anti-CD154 treatment could abrogate the production of alloantibodies [30]. CD154 is a key molecule in the contact-mediated signaling required for B cell activation and differentiation and can induce Ig isotype switching [31,32], while the CD27/CD70…”
Section: Nicolls Et Al Demonstrated That Combining Monoclonal Antibosupporting
confidence: 82%
“…One approach to successfully achieving long-term graft survival in murine cardiac allograft models is with anti-CD154 (MR1) mAb therapy (3)(4)(5)(6)(7)(8). Blocking CD40-CD154 interactions abrogates both naive B cell responses and T cell priming (9).…”
mentioning
confidence: 99%